Pengaruh Profitabilitas dan Ukuran Perusahaan Terhadap Penghindaran Pajak (Studi Empiris pada perusahaan Manufaktur Sub Sektor Otomotif yang terdaftar di Bursa Efek Indonesia Periode 2012 – 2017) - Linda Ayu Wulandari; Endang Mahpudin (IKOPIN, 2020)
This research aims to test the influence of profitability and size of the company with tax evasion. The population taken as the object of this research is as many as 13 companies in the automotive subsector Manufacturing Company with sampling method namely purposive sampling, so that the number of observations acquired as many as 9 companies. The results showed that the company's profitability and size were simultaneously influential against tax evasion. The partial profitability has no effect on tax evasion, and the company size partially affects the tax evasion on the automotive sub-sector manufacturing company listed on the Indonesia Stock exchange period of 2012-2017.